Nitrate levels in well water and population health risk of Kota Bharu and Bachok, Kelantan in different planting phases - Ahmad Roslan, Amirah; Mohamad Sham, Shaharuddin; Syed Ismail, Sharifah Norkhadijah (American-Eurasian Network for Scientific Information, 2014)
Background: Many researchers found exposure to nitrate increases the risk of getting cancer. Uncontrolled application of fertilizers on crops can cause excess nitrate to leach into groundwater. Objective: This study was conducted to determine nitrate levels in well water in paddy farming areas during three planting phases. The study also determined the health risk associated among population who worked and lived in the study area. Results: The mean±standard deviation of nitrate levels in Kota Bharu and Bachok was 2.69±2.43 mg/l and 4.02 ± 3.85 mg/l respectively, which was below the national standard (10 mg/l). In general, the highest nitrate concentration was found during planting season with the mean ± SD of 4.63±4.84 mg/l as compared to pre-planting (2.84±2.26 mg/l) and harvesting phase (2.51±2.90 mg/l). The highest nitrate concentration was found in Bachok during the planting season with the mean ± SD of 6.58±5.89 mg/l. The hazard index for the study population was less than 1 and ranged between 0.00 and 0.29. Conclusion: In conclusion, the levels of nitrate in well water in Kota Bharu and Bachok is acceptable and the population has minimal health risk.